Smart Energy Access and Women Empowerment: A Case Study of Chitandika Village in Zambia - Mantubwe Wampata; Bupe Getrude Mwanza (International Journal of Engineering and Management Research, 2021)
Smart energy access provides numerous advantages in rural areas such as economic development and improved livelihood. Despite the efforts by energy companies to supply to rural areas, women still face a range of constraints in their ability to participate in energy activities. Therefore, this study sought to analyze the goals of access to smart energy on women empowerment from the energy company perspective, assess the extent to which access to smart energy has contributed to empowerment and to establish the challenges faced by women in accessing smart energy with the intent of outlining strategies for future implementation. The study used a qualitative thematic analysis approach. The data was collected through structured, open-ended interviews with 20 women respondents with access to energy in chitandika village and 1 in-depth interview with the key energy expert. The study found that access to smart energy in chitandika village had a positive effect on women empowerment as it provided several benefits for the women. Additionally, the study established general and specific challenges that women face in accessing smart energy. Furthermore, it was established that the key strategies for implementing smart energy access on women empowerment were gender mainstream in energy projects, understanding women’s energy needs and demands, promoting productive use, supporting credit, and saving schemes and promoting skill development.